2022
DOI: 10.3389/fimmu.2022.705472
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicle/Macrophage Axis: Potential Targets for Inflammatory Disease Intervention

Abstract: Extracellular vesicles (EVs) can regulate the polarization of macrophages in a variety of inflammatory diseases by mediating intercellular signal transduction and affecting the occurrence and development of diseases. After macrophages are regulated by EVs, they mainly show two phenotypes: the proinflammatory M1 type and the anti-inflammatory M2 type. A large number of studies have shown that in diseases such as mastitis, inflammatory bowel disease, Acute lung injury, and idiopathic pulmonary fibrosis, EVs prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 134 publications
1
9
0
Order By: Relevance
“…MSCs-EVs are the hot spot of current research as they have been identified to inherit the anti-inflammatory and immunomodulatory properties of stem cells, inducing the M2 polarization of macrophages, reducing inflammation, while avoiding the disadvantage of stem cells such as tumorigenicity ( 46 ). Importantly, MSCs-EVs present a specificity of the EV/macrophage axis ( 46 ).…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs-EVs are the hot spot of current research as they have been identified to inherit the anti-inflammatory and immunomodulatory properties of stem cells, inducing the M2 polarization of macrophages, reducing inflammation, while avoiding the disadvantage of stem cells such as tumorigenicity ( 46 ). Importantly, MSCs-EVs present a specificity of the EV/macrophage axis ( 46 ).…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
“…MSCs-EVs are the hot spot of current research as they have been identified to inherit the anti-inflammatory and immunomodulatory properties of stem cells, inducing the M2 polarization of macrophages, reducing inflammation, while avoiding the disadvantage of stem cells such as tumorigenicity ( 46 ). Importantly, MSCs-EVs present a specificity of the EV/macrophage axis ( 46 ). In allergic rhinitis, human MSCs-EVs could inhibit the differentiation of Th2 cells via the regulation of the miR-146a-5p/SERPINB2 pathway ( 92 ), which shall be extrapolated for allergic inflammation of lower airways.…”
Section: Discussion and Future Research Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of pathogenesis, CEVs can act as a shuttle or biomarker for inflammation, and were involved in the progression of various tissue inflammation [ 42 ]. In terms of therapy, a large number of studies have shown that SCEVs and ICEVs (sEVs were mainly discussed below) have powerful immunomodulatory and anti-inflammatory effects on various inflammatory diseases such as periodontitis [ 43 , 44 , 45 ].…”
Section: Cevs and Periodontal Regenerationmentioning
confidence: 99%
“…The amount of integrin-beta 1-containing EVs is found to be elevated in NASH patients with mild fibrotic injury, compared to patients with steatosis, which is attributed to their association with monocytes recruitment. It has to be noted that the aforementioned phenomenon implies their possible use as disease biomarkers [ 66 , 67 , 68 , 69 ]. Moreover, the enhancement of chemotaxis and the aggravation of the inflammatory state is also induced by the transmembrane protein IRE1a, which induces the release of a great amount of EVs in the extracellular milieu.…”
Section: The Association Between Evs and Nashmentioning
confidence: 99%